Identifying subject thesauri as an educational tool for sustainable education - Navaneethakrishnan, S.; Arulanantham, S. (University Librarians’ Association, 2016)
In a rapidly changing world that is dominated and driven by knowledge, educational reforms occur at global and national level. Impacts of these reforms on the developing countries particularly on Sri Lanka have made an attention on the necessity of reconsideration and reformation of the education sector according to the current trend. In education, the skills and ideas are usually formed by means of the concepts to provide solutions of professional problems within an appropriate knowledge field. Education has to focus on teaching students ‘how to learn’ rather than emphasizing occupation specific knowledge. This study concentrates more on this specific scope with different level of education system. Accordingly, objective of this research is to propose the Subject thesauri as an appropriate educational tool for educational development in teaching and/or learning environment. The International Standard Organization (ISO) defines a thesaurus is a controlled and dynamic vocabulary of semantically and generically related terms which covers a specific domain of knowledge. In order to examine the thesauri concept at various levels with past experiences, current practices and predicts future trends of it, this study employed descriptive method with some theoretical analysis technique. Further datasheets and questionnaires were used for analysis of views of educational planners and students related with research scope. This study emphasis suitability of the basic elements of the thesauri concept for educational development and justify appropriateness of thesauri concepts to manage the educational reforms. Further this study supports policy makers by suggesting some educational models with thesauri concept to ease the forum. Findings of this study identified thesaurus as an appropriate educational tool for current education system. It plays various roles in a subject field. It is identified as a vocabulary tool which provides a standard vocabulary for the subject; as a ICULA 2016 University Librarians’ Association of Sri Lanka 71 Teaching tool which helps teachers to introduce the scope of their subject for new students with a tree structure; as a Learning tool which promotes learning and ultimately students’ progress and achievement; as a Research tool which guides researchers with classified hierarchies so that a literature search can be broadened or narrowed systematically; as a Retrieval tool which satisfies browsing and retrieval needs of a user community; and as a Literacy tool which increases literacy of users in various aspects such as information, language and media. As a summary it could be used to enable us to overcome the barrier between the practical application and the theoretical knowledge. Finally this study proposes the subject thesauri as an appropriate educational tool suitable for numerous educational structures to be developed for different levels of learners in South Asian context.
Keywords: Education; Information Literacy; Subject Thesauri; Sustainable Education